Religious Solidarity for Coping with Economic Crisis During the Covid-19 Pandemic - Luqman Luqman; Ilhamdi Ilhamdi (Al-Albab, 2022)
The COVID-19 pandemic has devastated the global and local economies. However, it has also contributed to the functioning of social solidarity in dealing with crisis pressure among local people which became a survival strategy for various businesses. This paper aims to map the patterns of economic pressure resulting from a pandemic and analyze social strength factor that became a survival strategy in the economic field. This research was conducted on several Chinese Indonesian converts to Islam [mu’alaf] to examine their religious solidarity that served as the strength for their survival as entrepreneurs. Therefore, qualitative research was conducted in a community of converts to Islam in Pontianak city, as one of the centers with a significant number of Chinese populations. In addition to data on crisis they experienced during the pandemic, this research also revealed their perceptions, motivation and actions in response to COVID-19. The results of the research showed that social and spiritual capital is the most important support that allows converts to recover from difficult times. Religion has become the moral basis of these entrepreneurs for solidarity and a source of support in coping with the pressure and problems. In the midst of scarcity of economic resources, religion-based social resources have become the answer to the problems encountered by these entrepreneurs.